(3QSGdI aj GdQO Ydi GdShaSWGFjIs - (3SYO Gddgs
(3ChdgG (B:s
(3bGd ehdGfG SYO Gddg QMeg Gddg NdGakG ddShaSWGFjI s
(3BNQgG (B:s
(3hGdeQGO Pdc hGdZadI hdjS eDef OCH GdYbdGA hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(116) s
Keywords: (3GdeLGejYs